Stadium architecture and regional economic development: International experience and the plans of Durban - Wolfgang Maennig; Florian Schwarthoff (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2006)
For the FIFA World Cup 2010, South Africa plans to invest heavily. The positive economic effects that the country is hoping for stand in contrast to almost all statistical ex-post studies. This contribution emphasises that these results, usually from research under-taken in the USA, can only be generalised to a limited degree. The density of sports venues in developed countries is so high, that the marginal effects of new stadia are necessarily limited. We also emphasise that stadium design around the world was not hitherto adequately targeted towards positive economic effects. The example of Durban and its plans for a new iconic stadium is used to illustrate fundamental principles of stadium design and their embedding in a re-urbanisation process that have to be undertaken in order to consciously achieve positive regional economic effects.
Keywords: 330; stadium architecture; regional economics; sports economics; World Cup; Durban